Hubungan Romantis dan Penyesuaian Sekolah di Kalangan Siswa SMP: Studi Fenomenologis - Adinda Ery Larasati; Lucia Rini Sugiarti; Ira Kusumawaty (Universitas Pahlawan Tuanku Tambusai, 2026)
Romantic relationships are one of the developments that start to emerge in early adolescence, including among junior high school students. Experiencing a romantic relationship can provide emotional support, boost self-confidence, and expand students' social skills. However, such relationships also have the potential to cause emotional conflicts that affect students' academic and social life at school. This study aims to explore the life experiences of junior high school students who are in romantic relationships and understand how these experiences influence their adjustment to school life. The study uses a qualitative approach with a phenomenological design. Participants consist of 12 junior high school students who have had at least three months of dating experience. Data were collected through semi-structured in-depth interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The results of the study are expected to show that romantic relationships are seen as a source of emotional support, a way to gain attention and social recognition, and a medium for learning about commitment and interpersonal communication. In addition, dating experiences affect school adjustment through changes in learning motivation, quality of relationships with peers, emotional management, and involvement in school activities. The research findings are expected to contribute to the development of guidance and counseling services that support adolescents' social-emotional development.